Impaired Nasal Mucociliary Clearance in Patients with Lichen Planus: Association with Mucosal Involvement - Emre, Elif; Temiz, Selami Aykut; Emre, Sadettin; Dundar, Mehmet Akif; Daye, Munise (Springernature, 2025)
Purpose Lichen planus (LP) is a chronic inflammatory disease affecting squamous epithelia, potentially impacting various epithelian surfaces, particularly the skin, oral mucosa, and nails. Mucosal involvement is clinically significant due to its influence on disease course and complications. Mucociliary activity plays a critical role in the defense mechanisms of the respiratory tract, and the potential impact of LP on this activity remains unknown. This study aims to investigate changes in nasal mucociliary activity (NMCT) in patients with LP and to examine the effects of any changes on respiratory health. Patients and methods The study included 30 patients with LP and 31 healthy controls. NMCT was measured using the saccharin transit time test. A 1 mm3 saccharin tablet was placed approximately 1 cm posterior to the anterior edge of the inferior turbinate in the left nasal cavity of each participant. NMCT was measured with a chronometer. Results NMCT in LP patients was 9.890 +/- 1.800 min, while in the control group, it was 7.835 +/- 1.530 min (p < 0.001). NMCT was significantly longer in LP patients with oral mucosal involvement compared to those without mucosal involvement (p = 0.044). NMCT tended to be longer in patients with nail involvement, but this difference was not statistically significant (p = 0.096). Conclusion Prolonged mucociliary clearance in patients with LP (especially those with mucosal involvement) may increase the risk of respiratory tract infections and negatively impact patients' quality of life. This finding highlights the importance of evaluating NMCT in LP patients and investigating potential therapeutic interventions to improve it.
Keywords: Lichen planus; Mucociliary activity; Oral mucosa; Mucociliary Clearance